Alcohol-Related Intentional Antiretroviral Nonadherence among People Living with HIV: Test of an Interactive Toxicity Beliefs Process Model. (19th February 2019) - Kalichman, Seth Charles; Katner, Harold; Hill, Marnie; Kalichman, Moira O'Connor; Hernandez, Dominica
Beliefs that it is harmful to mix medications with alcohol (ie, interactive toxicity beliefs) are a known source of intentional antiretroviral therapy (ART) nonadherence. This study examined a serial process model of alcohol-ART interactive toxicity beliefs, alcohol-ART avoidance behaviors, and ART adherence in the association between alcohol use and HIV viral load. Participants were 198 patients receiving ART from a community clinic in the southeastern United States; 125 reported current alcohol use. Results showed that current alcohol use was associated with detectable HIV viral load, partially accounted for by alcohol-ART interactive toxicity beliefs, alcohol-ART avoidance behaviors, and ART adherence. There was a significant indirect effect of the serial chain of interactive toxicity beliefs—avoidance behaviors—adherence, indicating the 3 intermediating variables partially accounted for the relationship between alcohol use and HIV viral load. Addressing alcohol use as a barrier to ART adherence requires multipronged approaches that address intentional nonadherence.